‘Japa’ Phenomenon And Nigeria Students In The Mix Of A Proxy War In Ukraine - William Abiodun Duyile; John Uzoma Nwachukwu (Britain International for Academic Research (BIAR) Publisher, 2023)
This study examined the Nigerian mentality, educational system, in context to migration as against the challenges faced by Nigerians in the Russo- Ukraine war in 2022. It also explains the ‘japa’ phenomenon and how foreign education is supporting migration. The research also traced the history of tertiary education in Nigeria. A retrospect and review of the facts was made, in order that scholars would have an insight on perceptions as well as the strategies anddiplomatic challenges Nigeria passed through in the course of this war. The study relied on documentary data. The documentary data were sourced from newspapers, journal papers, internet sources and correspondence. The documentary was subjected to internal and external criticism for authentication, and then to textual and contextual analyses. Nigerian students found themselves in a war that was never their making but the emigration from their nation to Ukraine made them a part of this piece of History.